Giant umbilical hernia case report and literature review - sanchez, Yankel A.; Garcia, Diana L. (International Journal of Research in Medical Sciences, 2022)
Umbilical hernia is a defect of the abdominal fascia that allows the protrusion of the intestinal content through the umbilical ring, in adults these hernias are associated with increased intra-abdominal pressure caused by obesity, abdominal distension, and abdominal distension. We presented the clinical case of a 38-year-old female patient who presented a giant umbilical hernia with contents of the transverse colon and necrotic ascending colon, performing abdominal wall plasty with separation of components. Treatment of patients with giant hernias is a challenge. The presence of non-viable bowel should not be considered a contraindication for mesh repair. Giant umbilical hernias are an uncommon pathology which requires knowledge of the different techniques of abdominal wall repair as well as their possible complications.